Different strategies to increase the biosurfactant production of a Paenibacillus sp. isolate (BR13834) (Research, Society and Development, 2021)
Biosurfactants are metabolites produced by several microorganisms, and in recent years are attracting interest in the scientific community due to their advantages over synthetic surfactants. The present study aimed to increase the production of biosurfactants by Paenibacillus sp., optimizing the growth factors carbon source, pH, temperature, and culture time. Initially, the carbon sources glucose, lactose, olive oil, soybean oil, glycerol, and kerosene were evaluated. Then, the factors pH, Temperature, and Time were evaluated, using a factorial design to identify the factors that influence the process of biosurfactant production. Finally, the environmental factors temperature and cultivation time were evaluated using central composite rotational design (DCCR). In all trials, the isolate BR13834 belonging to the genus Paenibacillus was used. The empirical prediction model developed was found to be adequate to describe biosurfactant production concerning surface tension (R2 = 0.755). The minimum value for surface tension was 34.6 mN/m, obtained under the optimal conditions of 30°C and 24 hours of cultivation. The results showed that DCCR was suitable to identify the best conditions for the production of biosurfactant produced by Paenibacillus sp.